Audit KKP Laporan Keuangan Puskesmas: Integrasi Akuntansi Terpadu Dan Pemeriksaan Akuntansi Sektor Publik - Nadia Putri, Sonya; Budiwitjaksono, Gideon Setyo (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This article aims to analyze the implementation of the Audit Working Papers (KKP) in the audit of Puskesmas financial statements by the Public Accounting Firm (KAP) Bambang, Sutjipto Ngumar and Partners and to examine its relevance to the concepts of integrated accounting and public sector auditing. This study employs a qualitative approach using participatory observation and semi-structured interviews. The results indicate that the implementation of the AWP has been appropriate in terms of audit documentation and evidence triangulation; however, it remains suboptimal in the utilization of information technology and the application of integrated accounting systems. Auditors still face limitations in manual systems that hinder data integration and audit effectiveness. These findings emphasize the importance of strengthening accounting information systems and digital audit training to improve the quality of public sector audits at Puskesmas. This article contributes to bridging the gap between theory and practice in public sector auditing based on empirical experience.